Adult patients with Ph+ ALL benefit from conditioning regimen of medium‐dose VP16 plus CY/TBI. Issue 5 (10th July 2022) - Morita‐Fujita, Mari; Arai, Yasuyuki; Kondo, Tadakazu; Harada, Kaito; Uchida, Naoyuki; Toya, Takashi; Ozawa, Yukiyasu; Fukuda, Takahiro; Ota, Shuichi; Onizuka, Makoto; Kanda, Yoshinobu; Maruyama, Yumiko; et al.
Abstract: The medium‐dose etoposide (VP16) added on cyclophosphamide (CY)/total body irradiation (TBI) is one of the intensified myeloablative conditioning regimens used in allogenic hematopoietic stem cell transplantation (allo‐HSCT) for acute lymphoblastic leukemia (ALL). However, the patient subgroups who can actually benefit from VP16/CY/TBI compared to CY/TBI have not been precisely defined. Therefore, we conducted a multi‐center retrospective study using the Japanese nationwide registry database to elucidate the efficacy of VP16/CY/TBI on post‐transplant prognosis. Biological and clinical distinct subtypes (i.e., Philadelphia chromosome‐positive (Ph+) and ‐negative (Ph−) ALL) were evaluated separately, which included 820 Ph+ and 1463 patients with Ph− ALL, respectively. Compared with the CY/TBI group, the VP16/CY/TBI group showed superior progression‐free survival (PFS) in patients with Ph+ ALL (65% vs. 57% at 3 years after HSCT; adjusted hazard ratio (HR), 0.73; 95% confidence interval (CI), 0.55–0.98; p = 0.03), along with significantly reduced incidence of relapse (adjusted HR, 0.58; 95% CI, 0.37–0.90; p = 0.02) without the increase of non‐relapse mortality (NRM). By contrast, in patients with Ph− ALL, VP16/CY/TBI did not improve PFS nor incidence of relapse; addition of VP16 reduced relapse (HR, 0.65; p = 0.06) in patients with Ph− ALL transplanted at CR1, while improved PFS was not observed (HR, 0.90; p = 0.52) due to increased NRM. This study demonstrated that VP16/CY/TBI is a more effective and well‐tolerated regimen in comparison with CY/TBI in patients with myeloablative allo‐HSCT for adult Ph+ ALL. Our findings can provide a novel algorithm for conditioning regimen selection in patients with adult ALL.